Revolutionizing biotechnology: the impact of nanocatalysts and nanomaterials—a comprehensive review - Abayomi Baruwa; Oluwatoyin Joseph Gbadeyan; Kugenthiren Permaul (Discover Materials)
Abstract Nanotechnology is an important advancement in materials science, primarily focused on the application of nanoparticles, especially in the nanoscaling of precious metals. This advancement has given researchers precise control over properties such as size, shape, composition, and morphology, leading to new breakthroughs in catalytic processes. While this concept is not new, the ongoing advancements in nanotechnology have made it a focal point in recent decades. Nanocatalysis is a powerful tool in modern science, offering better performance, longer lifespan, and easier recovery compared to traditional catalysts. Over the past 150 years, nanocatalysts have been called different names, such as colloids and clusters, but today, they are recognized for their unique properties that go beyond catalysis into many industries. Recent advancements in nanocatalyst synthesis have led to materials with special characteristics, such as a high surface area and increased reactivity due to more surface atoms being exposed. These properties make nanocatalysts excellent supports for attaching enzymes. When enzymes are immobilized on nanocatalysts (EnNPs), they become more stable and durable compared to free enzymes. The special features of nanocatalysts allow EnNPs to be used in various industries, improving enzyme efficiency in industrial processes. This article covers key methods for attaching enzymes to nanocatalysts and explores how their combination can enhance applications across different fields.